2019
DOI: 10.1007/s00044-019-02433-2
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, antimicrobial activity, and determination of the lipophilicity of ((cyclohex-3-enylmethylene)hydrazinyl)thiazole derivatives

Abstract: Synthesis and investigation of antimicrobial activity of fifteen novel thiazoles containing cyclohexene moiety are presented. Among the derivatives, compounds 3a-3d, 3f, 3n, and 3o showed very strong activity against the reference Candida spp. strains with MIC = 0.015-3.91 µg/ml. The activity of these compounds is similar and even higher than the activity of nystatin used as positive control. Compounds 3d, 3f, 3n, 3o showed the highest activity with very strong effect towards most of yeasts isolated from clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…The study revealed that compounds 50a, 50d, 50f, 50n, (Figure 18) showed a very good activity with MIC 0.015-3.91 μg/mL against C exhibiting equipotent or higher activity than nystatin used as the reference d highest activity was achieved in the case of compounds 50n and 50o with MIC 0.015-0.03 μg/mL/0.015-0.06 μg/mL. Thus, the presence of CH2COOEt and CH Biernasiuk et al [71] synthesized fifteen novel thiazoles containing cyclohexene moiety (Figure 18) and studied their antimicrobial activity against a panel of seven Gram-positive, seven Gram-negative bacteria, and four fungal Candida species as well as 14 clinical isolates. The study revealed that compounds 50a, 50d, 50f, 50n, and 50o (Figure 18) showed a very good activity with MIC 0.015-3.91 µg/mL against C. species, exhibiting equipotent or higher activity than nystatin used as the reference drug.…”
Section: Thiazole Derivatives As Antimicrobial Agentsmentioning
confidence: 89%
See 1 more Smart Citation
“…The study revealed that compounds 50a, 50d, 50f, 50n, (Figure 18) showed a very good activity with MIC 0.015-3.91 μg/mL against C exhibiting equipotent or higher activity than nystatin used as the reference d highest activity was achieved in the case of compounds 50n and 50o with MIC 0.015-0.03 μg/mL/0.015-0.06 μg/mL. Thus, the presence of CH2COOEt and CH Biernasiuk et al [71] synthesized fifteen novel thiazoles containing cyclohexene moiety (Figure 18) and studied their antimicrobial activity against a panel of seven Gram-positive, seven Gram-negative bacteria, and four fungal Candida species as well as 14 clinical isolates. The study revealed that compounds 50a, 50d, 50f, 50n, and 50o (Figure 18) showed a very good activity with MIC 0.015-3.91 µg/mL against C. species, exhibiting equipotent or higher activity than nystatin used as the reference drug.…”
Section: Thiazole Derivatives As Antimicrobial Agentsmentioning
confidence: 89%
“…It was obse the presence of lipophilic electrone-donating substituent (-CH3) in position 4 of nyl ring is more beneficial compared to hydrophilic, polar substituents (-CN, OH) as regards the antifungal activity. Biernasiuk et al [71] synthesized fifteen novel thiazoles containing cyc moiety (Figure 18) and studied their antimicrobial activity against a panel Gram-positive, seven Gram-negative bacteria, and four fungal Candida specie as 14 clinical isolates. The study revealed that compounds 50a, 50d, 50f, 50n, (Figure 18) showed a very good activity with MIC 0.015-3.91 μg/mL against C exhibiting equipotent or higher activity than nystatin used as the reference d highest activity was achieved in the case of compounds 50n and 50o with MIC 0.015-0.03 μg/mL/0.015-0.06 μg/mL.…”
Section: Thiazole Derivatives As Antimicrobial Agentsmentioning
confidence: 99%
“…All chemical reagents and solvents were purchased from Aldrich (Munich, Germany). Compounds 2 [ 54 ]; 3a,b [ 55 ] and 5a,b [ 11 ] were synthesized according to their previous method.…”
Section: Methodsmentioning
confidence: 99%
“…Hydrazinyl moiety possessing heterocyclic compounds displaying a wide spectrum of pharmacological activities which depend on the nature of incorporated substituent. Hydrazinyl derivatives display biological interesting as antioxidant [ 4 , 7 ], anti-inflammatory [ 8 ], anticonvulsant [ 9 ], analgesic [ 10 ], antimicrobial [ 11 , 12 ], anticancer [ 13 ], antiprotozoal [ 14 ], antiparasitic [ 15 , 16 ], cardioprotective [ 17 , 18 ], antitubercular [ 19 ] and anti-HIV [ 20 , 21 ]. Hydrazinyls derivative are used as common drug diseases for malaria [ 22 ], tuberculosis [ 23 ] and mental disorders.…”
Section: Introductionmentioning
confidence: 99%
“…It was more potent than Amphotericin B against C. neoformans and equipotent against both C. albicans and A. flavus.Using similar procedures, Biernasiuk et al synthesized a series of 2-hydrazinylthiazole compounds. 148 (Figure42) had a notable antifungal activity and was more potent than Nystatin against a variety of fungi strains including C. albicans (MIC 0.03 µg/mL), C. parapsilosis (MIC 0.03 µg/mL), C. krusei (MIC 0.015 µg/mL), C. inconspicua (MIC 0.06 µg/mL), and C. lusitaniae (MIC 0.06 µg/mL) 60.…”
mentioning
confidence: 99%